Multiple cerebral infarctions after intravenous immunoglobulin for Guillain–Barré syndrome: two case reports and review of the literature - Wang, Weisen; Feng, Chunhua; Liu, Yanqun; Tao, Yi; Bi, Xiaoying; Hou, Xiaojun (Frontiers in Immunology, 2024)
Guillain-Barré syndrome (GBS) is a polyradiculoneuropathy mediated by the immune system and is the primary reason for acute flaccid paralysis. Intravenous immunoglobulin (IVIg) is a recognized immunotherapeutic drug that can accelerate recovery from GBS.Limited literature exists concerning cerebral infarction complications with IVIg following its use in the treatment of GBS.Case presentation: A patient was diagnosed with the acute inflammatory demyelinating polyradiculoneuropathy subtype of GBS, while another patient was diagnosed with the acute bulbar palsy variant of GBS 2 years prior and experienced a relapse of GBS. Both patients received immunoglobulin therapy, during which multiple acute cerebral infarctions were detected using magnetic resonance imaging. Both patients had a history of coronary artery atherosclerotic heart disease and vertebral artery stenosis, and D-dimer and fibrinogen degradation products were significantly elevated after immunoglobulin therapy.Conclusions: The risk of cerebral infarction associated with IVIg is generally low in patients with different GBS variants. Nevertheless, the occurrence of cerebral infarction associated with IVIg might not be insignificant in older patients with vascular risk factors and should be carefully monitored.